Design and Performance Test of a Magnetic Rate Controlled Stage Damper - Yu, Guo-Jun; Zhu, Shao-Jie; Du, Cheng-Bin; Wang, Ling-Yun; Huang, Jun-Chi (Frontiers in Materials, 2021)
In order to control the vibration of civil building structures, a magnetic rate controlled stage damper (MRCSD) is designed based on magnetorheological shear thickening fluid (MR-STF). The key technology and performance test of the damper and the parameter identification of the mechanical model are studied. The experimental results show that the main cylinder filled with MR-STF combines MR effect and shear thickening effect, which has a strong effect of impact energy dissipation and vibration reduction. Therefore, the designed damper is superior to the traditional viscous damper. With the increase of magnetic field strength, the shear thickening effect of MR fluid is inhibited and the MR effect is more obvious. The MRCSD can improve the performance of vibration isolation and vibration reduction by controlling damping. Under different intensity of earthquake, the maximum output can reach 250.2 kN. The mechanical model of the MRCSD is established, and the design parameters of the damper are determined. The theoretical results obtained from the mechanical model of the MRCSD are basically consistent with the experimental results, which show that the parameter identification method is feasible and effective.